Effects of broken affordance on visual extinction - Wulff, Melanie; Humphreys, Glyn (Frontiers in Human Neuroscience, 2015)
Previous studies have shown that visual extinction can be reduced if two objects are positioned to “afford” an action. Here we tested if this affordance effect was disrupted by “breaking” the affordance – if one of the objects actively used in the action had a broken handle. We assessed the effects of broken affordance on recovery from extinction in eight patients with right hemisphere lesions and left-sided extinction. Patients viewed object pairs that were or were not commonly used together and that were positioned for left- or right-hand actions. In the unrelated pair conditions, either two tools or two objects were presented. In line with previous research (e.g., Riddoch et al., 2006), extinction was reduced when action-related object pairs and when unrelated tool pairs were presented compared to unrelated object pairs. There was no significant difference in recovery rate between action-related (object-tool) and unrelated tool-tool pairs. In addition, performance with action-related objects decreased when the tool appeared on the ipsilesional side compared to when it was on the contralesional side, but only when the tool handle was intact. There were minimal effects of breaking the handle of an object rather than a tool, and there was no effect of breaking the handle on either tools or objects on single item trials. The data suggest that breaking the handle of a tool lessens the degree to which it captures attention, with this attentional capture being strongest when the tool appears on the ipsilesional side. The capture of attention by the ipsilesional item then reduces the chance of detecting the contralesional stimulus. This attentional capture effect is mediated by the affordance to the intact tool.